1995
DOI: 10.1161/01.atv.15.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden Gene Mutation and Thrombin Generation in Relation to the Development of Acute Stroke

Abstract: To determine the prevalence of the factor V Leiden gene mutation in relation to the phenotypes of cerebral infarction and cerebral hemorrhage, we studied 386 randomly selected cases of acute stroke and 247 control subjects. Factor V genotype was determined by amplification of a 267-bp sequence of exon/intron 10 of the factor V gene. Levels of prothrombin fragment F(1 + 2), a marker of thrombin generation, were determined in both acute and convalescent stroke and related to factor V genotype. Prothrombin fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 7 publications
6
51
1
4
Order By: Relevance
“…Whereas a relationship has been documented in younger adults or specific settings, 16 -19,21 the presence of the FV Leiden mutation was not associated with stroke in studies that enlisted older adults or elderly patients. [22][23][24][25][26][27] For example, Catto et al 24 studied 386 randomly selected elderly patients (median age, 74 years) with acute stroke. In the present study, median age was 39 years, 25.8% of women and 20% of men aged 30 years or less when the ischemic event took place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas a relationship has been documented in younger adults or specific settings, 16 -19,21 the presence of the FV Leiden mutation was not associated with stroke in studies that enlisted older adults or elderly patients. [22][23][24][25][26][27] For example, Catto et al 24 studied 386 randomly selected elderly patients (median age, 74 years) with acute stroke. In the present study, median age was 39 years, 25.8% of women and 20% of men aged 30 years or less when the ischemic event took place.…”
Section: Discussionmentioning
confidence: 99%
“…16 -21 However, these claims have been challenged. [22][23][24][25][26][27][28][29] We have investigated a relatively young (Յ50 years of age) population with a history of ischemic stroke, in whom a genetic and prothrombotic influence is conceivable to be most clearly evident, to assess the relationship with carriership of hereditary prothrombotic risk factors.…”
mentioning
confidence: 99%
“…Most studies on FVL and arterial thrombosis have demonstrated insignificant or borderline significant associations, some studies favoring a risk reduction in FVL carriers, [5][6][7][8][9][10][11][12][13][14][15][16] others an increase. The present study (1) estimated risk of thrombosis in atherosclerotic arteries (MI or IS) as well as risk of atherosclerosis without thrombosis (non-MI-ischemic heart disease [non-MI-IHD]) in FVL carriers, using a population-based study; (2) examined if FVL interacts with established cardiovascular risk factors in predicting MI, IS, and non-MI-IHD; and finally (3) systematically combined our data with previously published studies on FVL and risk of arterial thrombosis using meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that coagulation disorders are the major cause of only a minority (1% to 4%) of all ischemic strokes 13,[22][23][24] but that they may be relevant to the pathogenesis of subgroups of stroke patients such as strokes in young patients. [25][26][27][28][29] We hypothesized that although inherited thrombophilias in isolation or combination may be important causal risk factors for only a small minority of patients with ischemic stroke, they may be pathogenically relevant to a greater minority of patients with specific pathogenic subtypes of ischemic stroke that involve thrombosis, such as large artery atherothrombosis and embolism of thrombus from the heart, and not other causes of ischemic stroke.…”
mentioning
confidence: 99%